Membangun Atmosfir Belajar Siswa Ekstrovert & Introvert dengan Metode Active Learning Klop and Zonk - Maria Patricia Tjasmadi; Diana Ifan Sari Ledoh (Proceedings of The ICECRS, 2018)
Learning atmosphere is the situation and condition or atmosphere of the process of teaching and learning activities in a classroom. The ideal situation and condition is to create a cheerfull, communicative and educative atmosphere. This learning above requires a good cooperation between teachers and student and fellow students. In the class teaching and learning activities, teachers usually feel a significant difference from each student, their personality, habits and learning styles. There are two types of personality characteristic that stand out and contradict each other if viewed from the psychological aspects. The first characteristic are students who are enthusiastic, active, courageous, and ask spontaneously. The second characteristic are shy, quite, and solitary students. If not addressed properly this defference will affect the process of teaching and learning activities. Based on the above exposure, teachers should be able to design a comfortable, interesting and creative learning environment in order to facilitate learning on both types of personality characteristics. The writer chooses active learning methods and designs klop and zonk media to create a fun learning atmosphere for all students, that aims to build the good learning atmosphere for ekstrovert and introvert students. To strengthen the method of active learning klop and zonk the writer has doing classroom action research for ekstrovert and introvert students.